NILAI-NILAI SUFISTIK TOKOH WAYANG SEMAR DAN IMPLIKASINYA TERHADAP PENDIDIKAN ISLAM - Rudy Al Hana; M. Yusuf (POTENSIA: Jurnal Kependidikan Islam, 2021)
This article aims to explain the Sufistic values contained in the wayang Semar character and their implications for Islamic education. Semar is a symbol of guardian and protector, for that his behavior is the same as that of the mursyid. The Sufistic values taught by Semar are shari'a or worship; tarekat or worship of the heart; essence or worship of the soul; makrifat or worship of taste; and mahabbah or holy love -asmarasanta. This indicates that what Semar is teaching is as characteristic of amali Sufism. Then Semar also teaches a sense of eling, sahid/ascetic, patient, and happy or sincere; this is also in accordance with the characteristics of akhlaqi Sufism. While the characteristics of philosophy as described by Semar with his teaching "manunggaling kawula lawan Gusti." The Sufistic values of the wayang Semar character contain philosophical, theoretical pedagogical, and praxis implications.